Validation of the assessment of computer task performance for children. - Mazer B; Dumont C; Vincent C (Technology & Disability, 2003)
Computers are often an important component of community integration for children with physical impairments; however, an accurate measure of functional computer ability is unavailable for those unable to normally access computers. This study aims to evaluate the psychometric properties of the Assessment of Computer Task Performance (ACTP), including test-retest reliability, construct validity, internal consistency, and discriminative validity. Participants were children with (n=24) and without (n=20) physical impairments, aged 4-13 years, who were experienced computer users. They were tested by a trained occupational therapist in either their home or school using the writing and pointer tasks of the ACTP. The test-retest reliability for the majority of tasks was high (ICC = 0.60-0.95), construct validity was strong, but internal consistency ranged from moderate to poor. Children with impairments took significantly longer to complete almost all computer tasks compared to the unimpaired group indicating good discriminative validity of the tasks. The ACTP provides therapists with an accurate measure to improve the delivery of computer access services for children. Future studies are needed to improve the test, particularly by including additional pointer tasks and by developing age-specific norms.